1983
DOI: 10.1007/bf00380601
|View full text |Cite
|
Sign up to set email alerts
|

Early indicators of renal damage in workers exposed to organic solvents

Abstract: In order to investigate the renal function, a cross-sectional study was carried out on four groups of workers significantly exposed to a mixture of alicyclic and aliphatic C5-C7 hydrocarbons, to styrene, to a mixture mostly composed of toluene and xylenes and to chlorinated hydrocarbons, respectively. The study involved 438 workers. Exposure was characterized by means of urinary metabolites, or by means of environmental measures, when biological indicators were not available. The renal function impairment indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
2
1

Year Published

1988
1988
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(48 citation statements)
references
References 19 publications
0
45
2
1
Order By: Relevance
“…In a similar study [42], four groups of solvent-exposed workers were examined for signs of renal impairment. The groups included 57 dry cleaners exposed to perchloroethylene, 118 painters exposed to benzene homologues, 51 boat and silo manufacturing employees ex posed to styrene and 212 shoemakers exposed to alkane hydrocarbons.…”
Section: Cross-sectional Epidemiologic Studies: Subtle Markers Of Renmentioning
confidence: 99%
“…In a similar study [42], four groups of solvent-exposed workers were examined for signs of renal impairment. The groups included 57 dry cleaners exposed to perchloroethylene, 118 painters exposed to benzene homologues, 51 boat and silo manufacturing employees ex posed to styrene and 212 shoemakers exposed to alkane hydrocarbons.…”
Section: Cross-sectional Epidemiologic Studies: Subtle Markers Of Renmentioning
confidence: 99%
“…Most of these studies concerned painters exposed to several solvents, but others involved printers whose solvent exposure was limited almost exclusively to toluene (table 1). The studies of painters have yielded contradictory results, glomemlar and tubular renal alterations being found in 3 studies (9-1 I), tubular alterations only in 2 others (12,13), and no effect in the final 2 (14,15). Different exposure levels did not explain the variations.…”
mentioning
confidence: 99%
“…Additional epidemiological studies have shown increases in kidney cancers (Katz and Jowett, 1981;Duh and Asal, 1984;Antilla et al, 1995). Studies of workers exposed to low concentrations of TETRA have reported increased urinary levels of lysozyme, albumin, ␤-glucuronidase, and the brush-border membrane antigens B50, BBA, and HF5 (Franchini et al, 1983;Mutti et al, 1992). Another study of Dutch workers exposed to TETRA at levels well below the Dutch occupational exposure limit (7.9 versus 240 mg/m 3 ) showed increased levels of retinol-binding protein compared with controls (Verplanke et al, 1999).…”
mentioning
confidence: 99%